MENILAI TINGKAT KESIAPAN PENERAPAN SMART AND COLLABORATIVE OFFICE (SCO) DENGAN PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL (TAM) - Hakim, Luqman; Oktavianto, Hardian; Dasuki, Moh (IPTEQ, 2022)
Smart Collaborative Office is a form of information system developed to support work activities within the Universitas Brawijaya. The main objective of this research is to assess the level of implementation of Smart and Collaborative Office (SCO) by using the Technology Acceptance Model (TAM) approach. Using quantitative methods, research instruments were developed based on the literature and previous empirical results related to TAM. A total of 98 respondents, namely Educational Personnel who work at the Head Office or Rectorate of Universitas Brawijaya, were the samples in this study. The research findings show that the ease of use of SCO is the most important predictor of intention to use SCO, while intention to use SCO is the most important determinant of the level of use of SCO at the Head Office of Universitas Brawijaya. The conclusion of the study is that in general the level of application of SCO can be categorized at a moderate level, including considering that the majority of respondents have never completed or attended SCO training.